Proof of concept for high-dose Cannabidiol pretreatment to antagonize opioid induced persistent apnea in mice - Wiese, Beth M.; Bondarenko, Evgeny; Feldman, Jack L. (Frontiers in Neuroscience, 2025)
BackgroundOpioid related fatalities remain a public health crisis in the US. Currently, the only way to restore breathing following an opioid induced persistent apnea is with the administration of the opioid antagonist naloxone, but it also reverses analgesia, euphoria, and induces precipitated withdrawal in opioid dependent individuals.MethodsUsing whole-body plethysmography, we assessed changes in breathing frequency in awake behaving mice resulting from a single fentanyl dose (50 mg/kg i.p.) that followed i.p. pretreatment with saline, vehicle, naloxone (100 mg/kg), cannabidiol (CBD) (250 mg/kg), or CBD + naloxone. Then we assessed the delay to opioid-induced persistent apnea (OIPA) and the median lethal dose (LD50) of fentanyl during a continuous i.c.v. infusion of fentanyl (100 ng/min), in urethane anesthetized mice, following pretreatment with saline, vehicle, naloxone (100 mg/kg), CBD (250 mg/kg), or CBD + naloxone i.p.ResultsHere we show acute pretreatment with CBD is as effective as naloxone at preventing opioid-induced respiratory depression from fentanyl in awake mice, and increasing LD50 of fentanyl in urethane anesthetized mice. When pre-administered together, CBD + naloxone, increased LD50 of fentanyl even more than CBD or naloxone alone in urethane anesthetized mice.ConclusionCBD may be an effective preventative therapy for OIPA by increasing the time before apnea onset and potentially enhancing the efficacy of naloxone as an additional strategy to save lives.